The Influence of Education and Training (Diklat), Work Motivation and Work Commitment on Employee Work Productivity at the West Sulawesi Provincial Youth and Sports Office - Rauf, Andi Saiful; Sapiri, Muhtar; Rahardjo, Djoko (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to explore the influence of education and training (diklat), work motivation, and work commitment on the work productivity of employees at the West Sulawesi Provincial Youth and Sports Office. The study was conducted by involving 47 respondents and using a questionnaire method which was then analyzed by multiple linear regression analysis. The results of the study show that education and training (diklat) have a positive influence on the work productivity of employees at the West Sulawesi Provincial Youth and Sports Office. In addition, work motivation and work commitment also significantly contribute to increasing the work productivity of employees in the agency. Finally, when analyzed together, education and training (diklat), work motivation, and work commitment collectively affect the work productivity of employees at the West Sulawesi Provincial Youth and Sports Office. These findings provide a deeper understanding of the factors that affect the work productivity of employees in the government environment, especially in the fields of youth and sports. The implications of this research can help in the formulation of human resource management policies and strategies aimed at improving organizational performance and effectiveness